1999
DOI: 10.1002/(sici)1097-0193(1999)8:1<28::aid-hbm3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

PET study of the human foveal fixation system

Abstract: Positron emission tomography (PET) was used to investigate the functional anatomy of the foveal fixation system in 10 subjects scanned under three different conditions: at rest (REST), during the fixation of a central point (FIX), and while fixating the same foveal target during the presentation of peripheral visual distractors (DIS). Compared with the REST condition, both FIX and DIS tasks activated a common set of cortical areas. First, in addition to the involvement of the occipital visual cortex, both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 93 publications
0
25
0
1
Order By: Relevance
“…Our results involving left FEF suggest that there may be bilateral differences in the functional role of FEF: left FEF may participate in maintenance of the spatial location of a stimulus, while right FEF participates in response preparation and execution processing. An alternative explanation is that the left FEF may be involved in processes related to holding fixation on the central crosshair during the delay period (Petit et al, 1999), which could result in a time course pattern similar to our maintenance-related pattern.…”
Section: Discerning Functional Roles Based On Differences In the Timementioning
confidence: 50%
“…Our results involving left FEF suggest that there may be bilateral differences in the functional role of FEF: left FEF may participate in maintenance of the spatial location of a stimulus, while right FEF participates in response preparation and execution processing. An alternative explanation is that the left FEF may be involved in processes related to holding fixation on the central crosshair during the delay period (Petit et al, 1999), which could result in a time course pattern similar to our maintenance-related pattern.…”
Section: Discerning Functional Roles Based On Differences In the Timementioning
confidence: 50%
“…Lobel et al (2001) localized the stimulation-defined FEF slightly more posterior and deeper (within the precentral sulcus) than previous stimulation studies, and thus closer to the site as proposed by fMRI. Yet in 75% of the subjects investigated by Lobel et al the stereotactic coordinates of the stimulation-defined FEF was still found anterior to the range of the FEF as defined by 17 fMRI studies (see Petit et al 1999;Blanke et al 2000). At present, it can thus not be decided whether this anatomical disagreement between studies using fMRI and ECS or transcranial magnetic stimulation might be due to methodological differences inherent in the two brain mapping techniques or to differences in examined oculomotor behavior as discussed previously (Luna et al 1998;Blanke et al 2000;Tehovnik et al 2000;Disbrow et al 2000).…”
Section: Anatomical Considerationsmentioning
confidence: 88%
“…Studies using functional magnetic resonance imaging (fMRI) (Darby et al 1996;Petit et al 1997;Luna et al 1998; but see reviews Paus 1996;Schall 1998;Petit et al 1999;Tehovnik et al 2000) and human lesions studies (Rivaud et al 1994;Ploner et al 1999) have situated the FEF along the precentral sulcus extending onto the precentral gyrus. A different site anterior to the precentral sulcus on the posterior part of the middle frontal gyrus has been proposed from studies using ECS (Förster 1931(Förster , 1936Rasmussen and Penfield 1948;Godoy et al 1990;Blanke et al 2000) and from a study using transcranial magnetic stimulation combined with 3D-MRI (Ro et al 1999).…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…Two studies comparing the fixation of a central target with eyes open in darkness (effectively simulating the difference between saccadic intrusion amplitude with the visual target light on or off) have been performed on healthy volunteers. One positron emission tomography study [34] found bilateral activations of the frontal eye fields and intraparietal sulcus as well as activations of the right frontal cortex when comparing patients fixating a central target compared to eyes open in darkness, while a functional magnetic resonance imaging study [16] found increases in occipito-temporal areas instead. Saccadic intrusions are thought to be generated from the saccadic system due to their similarity to saccade main sequence plots [12] and results from lesional studies have suggested that the rostral superior colliculus and basal ganglia both appear to have a role to play in maintaining fixation and inhibiting unwanted saccades.…”
Section: Discussionmentioning
confidence: 99%